NOTIFICATION OF SECURITY THREATS ON THE INTERNET PROXY SERVER IS A SERVER-BASED SHORT MESSAGE SERVICE (SMS ) - Mario Agapito Arizald Gobel; Sumarsono Sumarsono; Yuliani Indrianingsih (Compiler, 2012)
Defense system against interference when the activity is generally done manually by the administrator. This resulted in the integrity of the system depends on the availability and speed of the administrator in response to disturbance. In the current era of information technology, almost all information is important for an institution can be accessed by its users. Disclosure of such access raises new security issues in part of a computer network system that is very important to maintain the validity and integrity of data and ensure availability of services for its users.In this issue then designed a system to detect any interference. The detection is based filtering on the port service, using the programming language Delphi 7. The data obtained from the filtered traffic data packets passing the proxy server. By building a system that can work automatically and in real time, then perform the detection of intruders or illegal activities which will then be reported to the administrator.With this administrator can find out the use of illegal ports through port filter techniques on the traffic data service in and out in real time, from both internal and external networks. Administrators can do the monitoring without having to depend on availability. With such a system administrator can perform tasks more efficiently in maintaining the validity and integrity of data.